(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Obesity has emerged as one of the most significant global health challenges of the twenty-first century, with profound metabolic, cardiovascular, and immunological consequences. Beyond its well-established association with type 2 diabetes mellitus, hypertension, and cardiovascular disease, obesity is now increasingly recognized as a state of chronic low-grade systemic inflammation. This inflammatory milieu plays a critical role in the pathogenesis and progression of multiple immune-mediated and degenerative disorders, including a broad spectrum of rheumatologic diseases.